Analisis Penerapan Kepemimpinan Visioner Terhadap Performa Pegawai Pada Sekretariat Daerah Kabupaten Lamongan - Puji Dariani; Suyitno Suyitno; Rudi Wibowo (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to analyze the influence of visionary leadership on employee performance at the Lamongan Regency Regional Secretariat. This topic is important because effective leadership in the public sector is indispensable to improve employee performance and achieve organizational goals. This study uses a qualitative descriptive approach with in-depth interviews with 8 informants working at the Regional Secretariat. The data collected was analyzed using thematic analysis techniques to explore employees' perceptions of the application of visionary leadership and its impact on their performance. The main findings of this study show that visionary leadership improves employee performance through a clear vision, empowering employees to innovate, and increasing collaboration and motivation. Although challenges such as differences in perceptions of vision remain, overall, the implementation of visionary leadership has succeeded in creating a more positive and productive work climate. This research contributes to the development of leadership theory in the context of local government and provides practical insights for policy makers in designing more effective leadership strategies. In conclusion, visionary leadership can improve organizational performance in the public sector, but further research with a larger, more diverse sample is needed to expand on these findings.